Inspiratory muscle training improves strength and health-related quality of life in hemodialysis patients - Soares, Viviane; Oliveira-Silva, Iransé; Silva, Maria Sebastiana; Venâncio, Patrícia Espíndola Mota; Oliveira, Luís Vicente Franco; Lima, William Alves; Júnior, Jairo Teixeira; Tolentino, Grassyara Pinho; Bizinotto, Thailyne (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Patients undergone hemodialysis (HD) suffer with energy-protein malnutrition, uremic myopathy and protein catabolism reducing their functional capacity, tolerance to exercise and aspects related to quality of life. Objective: The aim of this study was to evaluate the effects of the two protocols of inspiratory muscle training (IMT) on muscle strength, pulmonary function and related-health quality of life on male HD patients. Methods: Maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP), peak expiratory flow (PEF), forced expiratory volume in first second (FEV1 ), forced vital capacity (FVC) and the FEV1 /FVC ratio and quality of life were evaluated pre and post six months of IMT in HD patients. IMT was performed by one group using a specific training (Power breathe) device (T-IMT, n=19) and by the other with incentive spirometry (I-IMT, n= 15). Results: Following the inspiratory training, muscle strength improved in both groups. The group that used incentive spirometry had increments in MIP larger (39.8%, p<0.001) than the group that trained with the specific training device (28.3%, p=0.001). The KDQOL-SF dimensions showed significant difference in the T-IMT group in cognitive function (p=0.03), sexual function (p=0.009) and social function dimensions (p=0.04) and in the I-IMT group in the physical function dimension (p=0.03). Conclusion: It was proved that IMT improved muscle strength and I-IMT promoted increments significantly larger in MIP. Aspects of health-related quality of life of HD male patients improved significantly with T-IMT (sexual, social and cognitive functions), while I-IMT ameliorated only physical function.